A New Class of Wideband Quadrature Coupled-Line Forward Couplers - Henning Mextorf; Winfried Schernus (IEEE Journal of Microwaves)
This paper presents a new class of wideband quadrature coupled-line forward couplers making use of the unequal phase velocities of even- and odd-mode of coupled-lines in inhomogeneous media. The proposed approach allows for the design of wideband quadrature couplers with arbitrary coupling ratios. The fundamental structure composed of two sections of strongly coupled lines and a section of ideally uncoupled lines is systematically analyzed and closed form equations for the synthesis of the design parameters are presented where possible. Multisection couplers designed by cascading the fundamental structure are investigated. They provide more design flexibility and an enhanced operating bandwidth. Two experimental prototypes exhibiting wide operating bandwidth up to 39% and flat magnitude and phase response are presented.